VD_FINDINFO Jug / 2019 / 165 vom 27. Februar 2019 - VD Tribunal cantonal (2019)
VIOL, PRINCIPE DE L'ACCUSATION, PRÉSOMPTION D'INNOCENCE, PRINCIPE DE LA CÉLÉRITÉ, FIXATION DE LA PEINE | 190 CP, 198 CP, 11 CPP (CH), 5 CPP (CH), 9 CPP (CH)